Effect of flecainide derivatives on sarcoplasmic reticulum calcium release suggests a lack of direct action on the cardiac ryanodine receptor. (29th June 2016) - Bannister, Mark L; Alvarez‐Laviada, Anita; Thomas, N Lowri; Mason, Sammy A; Coleman, Sharon; du Plessis, Christo L; Moran, Abbygail T; Neill‐Hall, David; Osman, Hasnah; Bagley, Mark C; MacLeod, Kenneth T; George, Christopher H; et al.
Abstract: Background and Purpose: Flecainide is a use‐dependent blocker of cardiac Na + channels. Mechanistic analysis of this block showed that the cationic form of flecainide enters the cytosolic vestibule of the open Na + channel. Flecainide is also effective in the treatment of catecholaminergic polymorphic ventricular tachycardia but, in this condition, its mechanism of action is contentious. We investigated how flecainide derivatives influence Ca 2 + ‐release from the sarcoplasmic reticulum through the ryanodine receptor channel (RyR2) and whether this correlates with their effectiveness as blockers of Na + and/or RyR2 channels. Experimental Approach: We compared the ability of fully charged (QX‐FL) and neutral (NU‐FL) derivatives of flecainide to block individual recombinant human RyR2 channels incorporated into planar phospholipid bilayers, and their effects on the properties of Ca 2 + sparks in intact adult rat cardiac myocytes. Key Results: Both QX‐FL and NU‐FL were partial blockers of the non‐physiological cytosolic to luminal flux of cations through RyR2 channels but were significantly less effective than flecainide. None of the compounds influenced the physiologically relevant luminal to cytosol cation flux through RyR2 channels. Intracellular flecainide or QX‐FL, but not NU‐FL, reduced Ca 2 + spark frequency. Conclusions and Implications: Given its inability to block physiologically relevant cation flux through RyR2 channels, and its lack of efficacy in blocking the cytosolic‐to‐luminal current, the effect of QX‐FL on Ca 2 + sparks is likely, by analogy with flecainide, to result from Na + channel block. Our data reveal important differences in the interaction of flecainide with sites in the cytosolic vestibules of Na + and RyR2 channels.